Frequency of deep vein thrombosis in women over 40 years old with breast cancer undergoing chemotherapy referred to Tabriz chemotherapy clinics in 2018 - Dara Alvandfar; Hasan Mohammadipour Anvari; Mahdi Nazari (Mashhad University of Medical Sciences, 2020)
Introduction: Increasing age and receiving chemotherapy are among the risk factors for deep vein thrombosis that have not been studied so far in Iranian society. Therefore, this study was performed with aim to investigate the frequencyof deep vein thrombosis in women over 40 years with breast cancer undergoing chemotherapy referred to Tabriz chemotherapy clinics in 2018. Methods: This cross-sectional descriptive study was performed on 165 women in Tabriz chemotherapy clinics in 2018. Deep vein thrombosis was assessed by the criteria for diagnosis of deep vein thrombosis and those who were at high risk of developing deep vein thrombosis were examined by Doppler ultrasound. Data were analyzed by SPSS software (version 21) and Spearman correlation coefficient and regression. PResults: The mean of deep vein thrombosis was 13.69±2.20 that based on the available checklist, 19 patients (11.52%) were at high risk for this complication that after Doppler ultrasound analysis, deep vein thrombosis was confirmed in 17 patients (10.30%). The results of Chi-square test showed a statistically significant difference between the number of chemotherapy sessions and developing deep vein thrombosis (p=0.001). Conclusion: The prevalence of deep vein thrombosis in the present study was 10.30% in patients with breast cancer undergoing chemotherapy, which was related to the number of chemotherapy sessions.